2018
DOI: 10.1155/2018/3732753
|View full text |Cite
|
Sign up to set email alerts
|

A Conservative Weight Loss Intervention Relieves Bowel Symptoms in Morbidly Obese Subjects with Irritable Bowel Syndrome: A Prospective Cohort Study

Abstract: Background Irritable bowel syndrome (IBS) is common in subjects with morbid obesity; the effect of weight loss programs on bowel symptoms is largely unknown. Methods This prospective cohort study explored bowel symptoms, health scores, and biomarkers in subjects with morbid obesity during a six-month-long conservative weight loss intervention. Bowel symptoms were assessed with IBS-severity scoring system (IBS-SSS) and Gastrointestinal Symptom Rating Scale-IBS. Changes in all variables and associations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 39 publications
0
45
0
2
Order By: Relevance
“…Changes in eating behavior were however not addressed in the present study. Moreover, a recently published study by our group reported a reduction in overall symptoms, diarrhea and bloating during the pre-operative conservative weight loss intervention [ 17 ]. A limitation is that dietary data was recorded only once during that time period, and correlations between the changes in diet and changes in bowel symptoms could therefore not be performed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in eating behavior were however not addressed in the present study. Moreover, a recently published study by our group reported a reduction in overall symptoms, diarrhea and bloating during the pre-operative conservative weight loss intervention [ 17 ]. A limitation is that dietary data was recorded only once during that time period, and correlations between the changes in diet and changes in bowel symptoms could therefore not be performed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients received dietary and lifestyle counseling at enrolment as well as at the follow-up visits. The pre-surgery intervention has been described in more detail previously [ 17 ]. The patients also received oral and written information regarding the dietary principles to be followed after the surgery (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Some weeks later, they participated in weekly group meetings for seven weeks chaired by nurses, nutritionists, surgeons and a psychologist. The last three weeks before surgery, they followed a strict "crispbread diet" containing 4200 kJ of energy [15].…”
Section: Interventionsmentioning
confidence: 99%
“…The conservative weight loss intervention with group counselling and personalised lifestyle interventions was based on the weight loss programs used in most Norwegian obesity clinics in this period of time [16], with some small local changes from the national standard due to availability of personnel. The intervention was organised as a series of outpatient visits [16,17]. The intervention started with three outpatient consultations of one-hour duration with a nurse, a nutritionist and a physician.…”
Section: The Conservative Weight Loss Interventionmentioning
confidence: 99%
“…The dietary recommendations were based on a reduced daily energy intake and recommendation of food items with a high micronutrient content [17]. The participants were adviced to eat less sugar and fat and more fibre and protein.…”
Section: The Conservative Weight Loss Interventionmentioning
confidence: 99%